Prestasi Belajar Matematika Ditinjau dari Sikap dan Komitmen Diri Peserta Didik pada Pelajaran Matematika - Arif Rahman Hakim (Universitas Indraprasta PGRI, 2016)
This study aims to determine the effect of simultaneous attitude and commitment to self-learners towards mathematics achievement, to determine the influence of attitudes of students towards mathematics achievement, and to determine the effect of personal commitment to the achievement of learners studying mathematics. This research is a survey among students of class VII in Panglima Besar Soedirman International Islamic Junior High School (PBS-IIJHS). The sample in this study amounted to 67 learners were taken by random from a population of as many as 207 people affordadle learners. Instruments used in this research is by using a written test in the form of multiple choice questions and essays, as well as non test technique in the form of qoestionnaires which prior validated empirically. The data were analyzed descriptively and inferentially that prior testing its requirements analisis; the normality test, linearity and multicollinearity test. Based on the research results, it can be concluded that there is a significant influence between attitudes and self-learners commitment toward mathematics achievement. Then there is a significant influence learners’ attitudes toward mathematics achievement. As well as a significant influence learners’ commitment toward mathematics achievement.